RE-CONCEPTUALISING YOUTH CIVIC EDUCATION IN POST-WAR ARMENIA (Education in the 21st Century, 2025)
The purpose of the research is to examine the directions for improving civic education programs in Armenia. The postwar and post-pandemic context in Armenia has created new challenges and opportunities for rethinking education, and civic education as well. This article is an attempt to contribute to the scientific understanding of the directions for improving civic education of young people in Armenia, taking into account the main features of the post-war society. The re-conceptualising of civic education in Armenia is conditioned by the war and the pandemic, a combination of social transformations. This study shows that civic education should go beyond the scope of only transferring knowledge and become a platform for formation of identity, meaning, values and democratic engagement.The results of the research indicate that the patterns of participation remain uneven. Urban girls are more active, both before the war and in the post-war period. This clarifies the necessary strategy for the differentiated development of inclusion for rural youth. Interactive and problem-based learning forms are the most effective methodologically. Teachers act as exemplary performers, therefore their choice and methodological structure should have. Civic education should maintain the connections of young people, promoting cooperation with local structures and ensuring the continuity of programs. At the same time, there are challenges.The latest technologies have become the core of modern citizenship, affecting awareness, political participation and social relations. Therefore, the purposefulness and methodological right of civic education should become a combination of civic education and a critical understanding of technologies.This study contributes to the growing body of research on civic education in transitional societies, offering evidence-based recommendations for rethinking civic education in Armenia. It calls for inclusive, community-driven, and digitally integrated approaches that empower youth and reinforce democratic values in a postwar context.
Keywords: youth; participation; Armenian youth; civic education; digital participation; post-war society